Recall Compliance in the Clinical Periodontics Section of the University of the Philippines College of Dentistry Academic Year 2018-2019/Franchette Mae T. Ladera and Seleena V. Lim. - Lim, Seleena V.; Buenaventura, Criszel F. (2023)
Introduction. Compliance with appointments is necessary for maintenance of oral
health. In Clinical Periodontics, recall appointments are a crucial part of the
treatment plan. Hence, the aim of this study is to determine the recall compliance
in the Clinical Periodontics Section of the University of the Philippines College of
Dentistry within the A.Y. 2018-2019.
Methodology. A retrospective approach through records review was done to
conduct this research. Periodontal charts of patients in the college within the year
2018-2019 were reviewed. Chi-square test was used to compare the different
groups/diagnoses (clinically healthy, gingivitis, and periodontitis) and different recall
intervals with the recall compliance. The Chi-square test was used to determine if
there is a significant relationship between the variables.
Results. A total of 154 periodontal charts were analyzed for this study. 144 out of
154 (93.51%) missed their scheduled appointments based on the treatment plan
signed by the patient and approved by the attending faculty. Only ten (6.49%)
attended their scheduled recall based on the treatment plan and were considered
compliant. The average deviation of actual appointment from the scheduled
appointment is 41.2 days. Statistical analysis revealed there was no significant
relationship between diagnosis and recall compliance of patients in the Periodontics
Section of UPCD A.Y. 2018-2019. In addition, it was also determined there is no x
significant relationship between recall interval and recall compliance of patients in
the Periodontics Section during the same academic year.
Conclusions. Findings show that there is a high percentage rate of missed
appointments by patients in the Periodontics Section of UPCD A.Y. 2018-2019.
Noncompliance is a significant issue that must be investigated.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental appointments